From Transparency to Sustainability: The Role of Climate Change and Social Responsibility Disclosure in Enhancing Sustainable Performance - Khalaf, Ayad Jumaah; Khalaf, Ahmed Mohammed; Kadhim, Adel Muwafaq; Aswad, Ghalib Jlewey; Hindi, Waleed Khalid; Abdulateef , Dheyab Ahmed (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of climate change disclosure (CCD) and corporate social responsibility (CSR) on sustainable performance in Asian companies from 2018 to 2023, highlighting the growing demand for transparency in corporate environmental and social practices. Based on a sample of 1,623 companies and 9,738 firm-year observations, the study uses multiple regression analysis to evaluate the relationship between CCD, CSR, and sustainable performance. Firms with incomplete data were excluded to ensure accuracy. Results show that high-quality CCD and CSR significantly improve economic, social, and environmental performance. Better disclosure is linked to stronger outcomes across all sustainability dimensions. The focus on Asian firms between 2018 and 2023 may limit the applicability of results to other regions. The study provides empirical support for policymakers to enhance sustainability reporting standards. It also promotes investor confidence and encourages responsible corporate behaviour aligned with sustainable development goals. This research enriches the literature by exploring CCD and CSR as drivers of sustainability in emerging Asian markets, emphasizing transparency as a strategic path to long-term value.